Average radio spectral energy distribution of highly star-forming galaxies. Issue Volume 12:Issue S333(2017) (8th May 2018) - Tisanić, K.; Smolčić, V.; Delhaize, J.; Novak, M.; Intema, H.; Delvecchio, I.; Schinnerer, E.; Zamorani, G.
Abstract: The infrared-radio correlation (IRRC) offers a way to assess star formation from radio emission. Multiple studies found the IRRC to decrease with increasing redshift. This may in part be due to the lack of knowledge about the possible radio spectral energy distributions (SEDs) of star-forming galaxies. We constrain the radio SED of a complete sample of highly star-forming galaxies ( SFR > 100 M⊙ / yr) based on the VLA-COSMOS 1.4 GHz Joint and 3 GHz Large Project catalogs. We reduce archival GMRT 325 MHz and 610 MHz observations, broadening the rest-frame frequency range to 0.3-15 GHz. Employing survival analysis and fitting a double power law SED, we find that the slope steepens from a spectral index of α1 = 0.51±0.04 below 4.5 GHz to α2 = 0.98±0.07 above 4.5 GHz. Our results suggest that the use of a K-correction assuming a single power-law radio SED for star forming galaxies is likely not the root cause of the IRRC trend.